Prevalence of HIV and Hepatitis-B in the Out Patient Department of a Private Dental College Hospital Chennai, India - Ramya G1 , Pratibha Ramani2 , Jeevitha M3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Acquired Immunodeficiency syndrome caused by the Human Immunodeficiency virus is greatly prevalentin the Indian subcontinent. Hepatitis-B is another condition that is affecting the population. Healthcareprofessionals are at an increased risk of being exposed to such pathogenic infections. Having adequateknowledge towards the infection and appropriate preventive equipment such as vaccinations, masks, glovesis crucial in preventing spread of infection. The current study assessed the prevalence of HIV and hepatitis-Bconditions among the out patients visiting Saveetha Dental College. The study was performed in the outpatient department of Saveetha Dental College, Chennai, India. Data required for the study was procuredby reviewing patient records and analysed data of 86000 patients between June 2019 to March 2020. Thedata was sorted in excel and statistically analysed using the IBM SPSS software analysis and the resultstabulated. A prevalence rate of 3.2% was observed with regard to hepatitis-B in this study. The study showedfemale predilection with the mean age of this study being 41yrs. Prevalence of HIV was not observed in thisstudy.Healthcare professionals are at high stake of infection due to occupational exposure. Proper clinicalexamination, history of the patient, preventive gear, vaccination and sterility protocols must be ensured tominimize the spread of infection.